Research on the relationship between markers of iron metabolism in patients with hypochromic microcytic anemia - hoang, anhthuhoang; Nguyen, Dac Nghiem; Ha, Nu Thuy Duong; Nguyen, Van Quang; Phu, Thi Hoa; Ta, Yen Dong; To, Thi My Chi; Van, Thi Thuy Hien; Le, Phan Minh Triet (Tạp chí Y Dược Huế, 2026)
Background: Hypochromic microcytic anemia (HMA) is a common condition with serious consequences if not detected and treated promptly. Hematological tests and biochemical indicators assessing iron metabolism help to identify the causes of HMA, especially iron deficiency anemia (IDA), hemoglobinopathy (HGP) and anemia of chronic disease (ACD). Objective: To determine several indicators assessing iron metabolism in HMA. Subjects and methods: A cross-sectional study was conducted on 168 patients with HMA who visited and received treatment at Hue University of Medicine and Pharmacy Hospital from January 2025 to January 2026, with three groups of causes including IDA, HGP and ACD. Results: The clinical manifestations of HMA were diverse. The most common symptom was pallor (48.2%), followed by fatigue (47.6%), anorexia (31.0%), dyspnea (19.0%). The cut-off values of serum iron, ferritin, transferrin saturation (TfS), unsaturated iron binding capacity (UIBC) in the prediction of HMA were 47.7 μg/dL, 112.7 μg/L, 13.7%, 50.0 μmol/L, respectively. The cut-off values of transferrin and TfS in the prediction of HGP were 274.5 mg/dL and 6.5%, respectively. Transferrin was an independent predictor of HGP and ACD, while serum iron and TfS were independent predictors of ACD. Conclusions: Patients with HMA exhibited heterogeneous clinical manifestations. Serum iron, ferritin, TfS, and UIBC were useful predictors of HMA. Transferrin independently predicted HGP and ACD, whereas serum iron and TfS independently predicted ACD.